How to plan an Italian grammar lesson through an eclectic approach - Peltekov, Peter (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
The present article describes the process of planning a grammar lesson in Italian using an eclectic approach. The lesson plan follows important grammar teaching principles and it is based on current research findings. Instead of following a specific method, it demonstrates how instructors can draw upon various approaches and theories to adapt the instruction to the learners’ needs and goals. Although the sample lesson plan is for teachers of L2 Italian, its classroom implications extend to the teaching of other languages. The main purpose of this article is to introduce novice language teachers to the activity of lesson planning and to encourage them to use research in education and applied linguistics to inform their teaching practices according to their teaching context.